1999
DOI: 10.1016/s0014-5793(99)00751-6
|View full text |Cite
|
Sign up to set email alerts
|

The cDNA cloning of human placental ecto‐ATP diphosphohydrolases I and II1

Abstract: The cDNA clones of two isoforms (enzymes I and II) of human placental ecto-ATP diphosphohydrolases have been isolated based on the N-terminal amino acid (aa) sequence of the immunopurified 82 kDa protein and characterized. The cDNA clone encoding enzyme I consists of 2081 nucleotides and the predicted enzyme I consists of 517 aa residues. Enzyme I has a 5P P-UTR and an N-terminal 11 aa sequence that differ from CD39, but the rest of the sequence is the same as CD39. The hydropathy plot indicated that enzyme I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…At the same time, the vascular NTPDase was identified as NTPDase1 [89]. A catalytically active human variant with an N-terminal sequence of 11 amino acids differing from CD39 was cloned from a human placenta cDNA library, whereas a truncated form lacking ACR5 was catalytically inactive [90,91]. The cell biology and function of these forms has not been further elucidated.…”
Section: General Molecular Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the vascular NTPDase was identified as NTPDase1 [89]. A catalytically active human variant with an N-terminal sequence of 11 amino acids differing from CD39 was cloned from a human placenta cDNA library, whereas a truncated form lacking ACR5 was catalytically inactive [90,91]. The cell biology and function of these forms has not been further elucidated.…”
Section: General Molecular Propertiesmentioning
confidence: 99%
“…Accordingly, transgenic mice expressing human NTPDase1 exhibited impaired platelet aggregation and were protected from thrombosis in a transplantation setting [179]. Moreover, adenovirus-mediated gene transfer of human placental NTPDase1 [91] into vascular smooth muscle cells was found to suppress thrombus formation and subsequent neointimal growth [180]. Similarly, gene transfer of this enzyme via cationic gelatin-coated stents inhibited subacute in-stent thrombosis and in addition suppressed neointimal hyperplasia and inflammation [181].…”
Section: Downstream Signaling Nucleotidesmentioning
confidence: 99%
“…Later, ATP diphosphohydrolase (or apyrase) was identified in human term placenta [81,198,316]. Two isoforms (enzymes I and II) of placental ecto-ATP diphosphohydrolases were later identified by cDNA cloning [263]. Four ATPases, which bind to ATP at the external surface of the membrane of syncytiotrophoblast brush boarder membranes, were described [54].…”
Section: Placentamentioning
confidence: 99%
“…The majority of the ecto-ATPDases that have been cloned are closely related to CD39, a cell surface antigen that is expressed on activated lymphocytes [11,12]. CD39s from several species have 60-90% identity in their primary sequences [12][13][14][15]. Biochemical and immunolocalization studies indicated that CD39s are vascular ecto-ATPDases [16][17][18][19][20].…”
mentioning
confidence: 99%